Success factors for FTTH deployment in Europe: Learning from the Leaders - Bernd Beckert (International Telecommunications Society (ITS), 2017)
Whereas broadband coverage with speeds of up to 30 Mbit/s is quite high, Europe is generally lagging behind in the roll-out of high-performance, future-proof fibre networks (Fibre-To-The-Home/ Fibre-To-The-Building). Yet, some European countries have been quite successful in their efforts to make FTTB/H connections available to their populations. This observation suggests the question, what strategies were applied and whether or not they could be applied in other countries as well.1 In order to find out about success strategies in selected FTTH leader countries we use a case study approach in which different factors like market structure, competition, regulation, policy intervention and demand are analysed. In the case studies, specific strategies which are of central importance for the selected countries are highlighted: In Estonia, we find that building a countrywide middle-mile-network as a public-private-partnership was a decisive move. In Sweden, municipality-owned city networks which have deployed fibre networks as Open Access Networks play an important role. In Spain it was hard regulation combined with a surge in demand which has lead to the "fibre-miracle". And in Switzerland, the countrywide roll-out of fibre networks is coordinated in a multi-stakeholder approach which was initiated by the national regulator. In the analysis part, six success strategies are derived from the empirical part, four of them originating directly from the respective countries and two being relevant in all selected countries. In the final part of the contribution, the recommendations are tested by applying them to the situation in Germany where FTTH coverage remains low.
Keywords: 330